2020
DOI: 10.1155/2020/1057167
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Antimicrobial Susceptibility Patterns of Diabetic Foot Infection of Patients from Bandar Abbas District, Southern Iran

Abstract: Diabetic foot infection is among the most common complications of diabetes mellitus which significantly causes hospitalization and is the most prevalent etiology of nontraumatic amputation worldwide. The current study aimed at assessing the frequency and antimicrobial susceptibility patterns of diabetic foot infection of patients from the Bandar Abbas area, in the south of Iran. In this study, a total of 83 diabetic patients with diabetic infected foot wounds referring to Shahid Mohammadi Hospital, Bandar Abba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 53 publications
1
4
1
Order By: Relevance
“…findings correlated with those of Djahmi et al and Bouharkat et al [13,15]. Studies in warm countries [Middle-East and North Africa (MENA) and south-east Asia] have found a higher prevalence of aerobic GNB [10,[16][17][18]. In contrast, studies from the western countries reported GPB to be the most frequently isolated pathogens [19,20].This discrepancy in the prevalence of GNB in DFIs between eastern and western countries remains largely unknown.…”
Section: Discussionsupporting
confidence: 78%
“…findings correlated with those of Djahmi et al and Bouharkat et al [13,15]. Studies in warm countries [Middle-East and North Africa (MENA) and south-east Asia] have found a higher prevalence of aerobic GNB [10,[16][17][18]. In contrast, studies from the western countries reported GPB to be the most frequently isolated pathogens [19,20].This discrepancy in the prevalence of GNB in DFIs between eastern and western countries remains largely unknown.…”
Section: Discussionsupporting
confidence: 78%
“…In a study by Talebi et al ( 2010), all S. aureus isolates were susceptible to vancomycin, but resistance of E. coli isolates to ceftriaxone was 88%, compared to 100% resistance observed in this study [22] . In a study by Ahmadishooli et al (2020) [23] , E. coli isolates were most sensitive to meropenem and least sensitive to ciprofloxacin, while in the present study, E. coli isolates showed the highest sensitivity to amikacin and imipenem and the lowest sensitivity to ceftriaxone. In a study by Dwedar et al (2015) in Egypt, the antibiotic susceptibility pattern was similar to that obtained in the present study, and the highest susceptibility of Gram-positive and Gram-negative bacteria was reported to vancomycin as well as imipenem and amikacin, respectively [24] .…”
Section: Discussioncontrasting
confidence: 49%
“…Similar findings were seen in a provincial hospital, where 64.29% of the bacteria were Gram-negative, with E. coli being the most frequent (16.07%), followed by S. aureus (14.29%) ( 15 ). Foreign countries also showed similar results, with E. coli being the most frequent bacteria in Iran with 20.5% ( 20 ), and Lebanon with 15% ( 21 ). Considering these reports, S. aureus, E. coli, and P. aeruginosa appear to be the most prevalent bacteria in diabetic foot infections worldwide.…”
Section: Discussionmentioning
confidence: 52%